Gene Expression Changes as Biomarkers of Immunosenescence in Bulgarian Individuals of Active Age - Dragomira Nikolova; Yana Todorova; Zora Hammoudeh; Blaga Rukova; Radoslava Emilova; Milena Aleksova; Vesselina Koleva; Maria Nikolova (Biomedicines)
Background/Objectives: Immunosenescence implies innate and adaptive immunity dysfunction, which naturally occurs with aging. It is a complex multifactorial process which can be triggered by either genetic changes, immune changes or both. Numerous research studies have shown that the process of senescence goes alongside chronic immune activation. The purpose of this study is to analyze the changes in the expression of genes associated with adaptive and innate immune responses in order to identify reliable biomarkers for immune aging. Methods: For that aim, 55 clinically healthy individuals of active age (21–65 years) were distributed based on immunophenotyping in two groups, with and without signs of premature senescence. A gene expression analysis was subsequently made on those two groups, and the differentially expressed genes were presented and interpreted. Results: Altogether, forty-eight (48) genes exhibited differential expression between the two groups, most of which showed up-regulation (45) (fold change more than 2), and only three were down-regulated (fold change less than −2). The highest positive fold change showed IL-1β (10.76), BCL6 (13.25) and CCL4 (15.91), while the highest negative fold changes were documented for IL23R (−3.10), IL5 (−2.66) and PTGS2 (COX-2) (−2.15). Conclusions: Our results reveal that immunosenescence is positively associated with chronic inflammation, which is typical for the aging process. On the other hand, we identified markers of possible protective effects against oxidative stress and tumorigenesis. These findings can aid the early diagnosis of chronic degenerative diseases in subclinical phase, as well as the development of strategies to prevent the processes of premature immune aging.